expand the following (x+1)(x+2),, (x-1)(x+2)​

Question

expand the following (x+1)(x+2),, (x-1)(x+2)​

in progress 0
Alexandra 1 month 2021-08-20T20:14:20+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-20T20:15:40+00:00

    Hey there

    Ans to the first one is x^2+3x+2

    And ans to second one is x^2+x-2

    0
    2021-08-20T20:16:03+00:00

    Answer:

    1) x^2 + 3x + 2

    2)x^2 + x – 2

    Step-by-step explanation:

    1st one,

    (x+1)(x+2) = x(x+2) + 1(x+2)

    = x^2 + 2x + x + 2

    = x^2 + 3x + 2

    2nd one,

    (x-1)(x+2) = x(x+2) – 1(x+2)

    = x^2 + 2x – x – 2

    = x^2 + x – 2

    If my answer helps you mark me as brain list and follow me.

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )